Anti-corruption mechanisms in the Maghreb: Algeria, Tunisia, Kingdom of Morocco - Mhamedi Bouzina, Amena (Journal of Human Sciences, 2022)
There are many forms and patterns of corruption that have spread widely in the world, especially in the Arab Maghreb region, and in this context, many questions arise about the reasons for the spread of this phenomenon in the countries of the Maghreb, so this research dealt with an evaluation of the role of anti-corruption mechanisms in the Maghreb countries of Algeria, Tunisia and the Kingdom of Morocco. Therefore, this study aims to shed light on the strategy followed by the Maghreb countries to confront corruption in the light of legal texts and to ascertain the extent of the effectiveness of these means in facing or combating corruption crimes by assessing the criminal policy in the field of fighting corruption and the prospects for its activation.